The Application Of The Principle Of Good Faith In Online Transactions As An Effort To Protect The Law Against Consumers - Pawestri, Ros; Heniyatun, Heniyatun; Sulistyaningsih, Puji; Praja, Chrisna Bagus Edhita (Prosiding University Research Colloquium, 2021)
The principle of good faith is one of the efforts to provide legal protection to consumers in onlinetransactions. This research aims to review andauthorize theapplication of the principle of goodfaith, and its legal protectionif consumers are harmed in online transactions. This research is expected to provide additional thought for all parties involved in transactions through online. The method used in this study is normative juridical, with data collection through literature studies and interviews. The results showed that the application of the principle of good faith by business actors in transactions through online is a very important thing, and must be implemented by the parties concerned, so that no party is lost. This is because good faith is the basis of business actors in making agreements to minimize losses for consumers. But in practice there are still many consumers who are harmed by business actors. Legal protection of consumers is based on Law No. 8 of 1999 on Consumer Protection and Law No. 19 of 2016 on changes to Law No. 11 of 2008 on Information and Electronic Transactions (ITE Law), namely what are the rights and obligations of business actors and comments, and how the provisions on online transactions to protect the interests of the parties. Legal efforts that can be done by consumers are settlements on a non-litigation basis or litigation.